Therapeutic Adventure Programming with Mixed Population in Cebu, Philippines - Hernani, Emmanuel V. (Silliman Journal, 2022)
This paper analyzed the experiences of 302 participants in a brief therapeutic adventure program sponsored by the social welfare institution of the Philippines. Participants were children victims of BCVTF XPNFOJOEJGmDVMUDJSDVNTUBODFT QFSTPOTXJUIEJTBCJMJUZ ZPVUI JO DPOnJDU XJUI UIF MBX BHFODZ XPSLFST BOE WPMVOUFFST 5IFQSPHSBNJODMVEFESJTLFYFSDJTFTXJUIJOUFSNJUUFOUEFCSJFmOH In-depth processing using Gestalt Therapy commonly asked RVFTUJPOT GPDVTFEHSPVQEJTDVTTJPO BOEQPTUBDUJWJUZJOUFSWJFX concluded the activity. Results showed the clients’ perceived effectiveness through learning outcomes on personal, relational, BOE PSHBOJ[BUJPOBM DPNQPOFOUT UFDIOJDBM FUIJDBM BOE DVMUVSBM JTTVFT TBMJFOU UP FYQFSJFOUJBM BDUJWJUJFT TQFDJmD UP UIF UZQFT PG clientele.